On the prediction of the mutual impact of business processes and enterprise information systems - Heinrich, Robert; Paech, Barbara (Software Engineering 2013, 2013)
Frequently, the development of business processes and enterprise information systems (IT systems) is not well aligned. Missing alignment of business process design and IT system design can result in performance problems at runtime. Simulation is a promising approach to support the alignment of the designs by impact prediction. Based on the predicted impact, the designs can be adapted to enable alignment. However, in current simulation approaches, there is little integration between business processes and IT systems. In this paper, we present a simulation-based approach to predict the impact of a business process design on the performance of IT systems and vice versa. We argue that business process simulation and IT simulation considered in isolation is not an adequate approach as this neglects the mutual impact on workload distribution. Furthermore, we sketch a solution idea to adequately represent workload distribution in simulation.
Gesehen am 12.06.2020